2021
DOI: 10.1016/j.sleep.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Delayed sleep–wake phase disorder in young adults: prevalence and correlates from a national survey of Norwegian university students

Abstract: Background: Delayed sleepewake phase disorder (DSWPD) during adolescence has been linked to impaired health and poor functioning. However there is a dearth of knowledge about DSWPD in young adulthood. We seek to contribute knowledge on the prevalence and correlates of DSWPD in this age group. Methods: Data were drawn from a 2018 national survey of students in higher education in Norway (the SHoT-study). All 162,512 fulltime students in Norway were invited to participate and 50,054 students (69.1% women) aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 50 publications
7
22
0
Order By: Relevance
“…3 DSWPD is prevalent in adolescents and young adults, with a prevalence of 7% to 16%. 4 , 5 Because most patients with DSWPD present with difficulty sleeping, they are often misdiagnosed as insomniacs by clinicians. 6 Previous data show that about 10% of recurrent insomnia patients in the sleep clinic are DSWPD.…”
Section: Introductionmentioning
confidence: 99%
“…3 DSWPD is prevalent in adolescents and young adults, with a prevalence of 7% to 16%. 4 , 5 Because most patients with DSWPD present with difficulty sleeping, they are often misdiagnosed as insomniacs by clinicians. 6 Previous data show that about 10% of recurrent insomnia patients in the sleep clinic are DSWPD.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a simple and useful assessment tool for the screening of DSWPD is desirable. To date, most epidemiological studies on DSWPD have employed a self-reported questionnaire based on the criteria items of the disorder on the ICSD (9,12,13). In this questionnaire, the information regarding the inability to fall asleep at the desired bedtime, which is mandatory for the clinical diagnosis of DSWPD, is lacking (9,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of DSWPD has been reported at 0.17%−1.5% in the general population (6,7). In comparison, a survey on 10,220 adolescents aged 16-18 years in Norway found a relatively higher rate of 3.3% (8), and a most recent Norwegian survey of 50,054 students aged 18-35 years showed a prevalence of 3.3% (9), suggesting that the disorder is possibly more prevalent in the younger generation than in other populations. The desired bed-off time of workers in their 20s is much earlier than that of university students (10), and the desynchronization of their sleep phase due to DSWPD may lead to maladaptation to their work life (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep problems such as insufficient sleep duration, sleep disturbance, and sleep‐wake problems are associated with behavioural problems, self‐harm behaviours, depressive symptoms, anxiety, and worse health‐related quality of life (HRQoL) in adolescents (Bøe et al., 2012; Roeser et al., 2012; Shimizu et al., 2021; Shochat et al., 2014; Sivertsen et al., 2021; Sivertsen et al., 2015). Reversely, behavioural problems and emotional disturbance are associated with difficulties in sleep onset and maintenance (Ivanenko et al., 2005; Meijer et al., 2010), thereby indicating a potential bidirectional relationship between sleep and mental health.…”
Section: Introductionmentioning
confidence: 99%